2022
DOI: 10.1101/2022.06.02.494472
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The reef-building coralGalaxea fascicularis: a new model system for coral symbiosis research

Abstract: Reef-building corals owe their evolutionary success to their symbiosis with unicellular algae (Symbiodiniaceae). However, increasingly frequent heat waves lead to coral mass-bleaching events and pose a serious threat to the survival of reef ecosystems. Despite significant efforts, a mechanistic understanding of coral-algal symbiosis functioning, what leads to its breakdown and what can prevent it, remains incomplete. The main obstacles are low amenability of corals to experimental handling and, owing to its ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…Raw sequencing data submitted to NCBI SRA BioProject PRJNA947274 Representative sequences (ASVs) submitted to NCBI GenBank Accession numbers OQ677536 to OQ677992 Additional data, scripts, and code are available online: https://doi.org/10.5281/zenodo.10551928 (Puntin 2024)…”
Section: Data Are Available Onlinementioning
confidence: 99%
See 1 more Smart Citation
“…Raw sequencing data submitted to NCBI SRA BioProject PRJNA947274 Representative sequences (ASVs) submitted to NCBI GenBank Accession numbers OQ677536 to OQ677992 Additional data, scripts, and code are available online: https://doi.org/10.5281/zenodo.10551928 (Puntin 2024)…”
Section: Data Are Available Onlinementioning
confidence: 99%
“…To include these critical features, research with corals is irreplaceable (Puntin et al 2022b). The reef-building coral Galaxea fascicularis (Linnaeus, 1767) has been proposed as a model species for coral symbiosis research (Puntin et al 2022a). This species is well represented in the literature, featured in studies that characterize the coral gastric cavity (Agostini et al 2012; Zhou et al 2020) and the calcification processes (Al-Horani et al 2003, 2005, 2007), among others (Ferrier-Pagès et al 1998; Niu et al 2016; Miura et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This ability to modulate symbiont state is valuable; however, to date, no studies have reported successfully inoculating A. poculata with different (i.e., heterologous) symbiont strains. While other studies have reported acquisition of novel algal symbionts in adult corals (Puntin et al 2022;Scharfenstein et al 2022), inoculation of A. poculata with heterologous algal strains should remain a priority.…”
Section: Further Develop Calcifying Coral Modelsmentioning
confidence: 99%
“…Several other reef building species are emerging as potential models, including Oculina arbuscula (Rivera and Davies 2021) and Galaxea fascicularis (Puntin et al 2022), which can also have their symbiotic states experimentally manipulated. In fact, G. fascicularis has been successfully bleached and then reinoculated with presumed heterologous strains of Symbiodiniaceae (Puntin et al 2022), providing a promising system to cross different host genotypes with algal strains as proposed above (Figure 2).…”
Section: Further Develop Calcifying Coral Modelsmentioning
confidence: 99%
See 1 more Smart Citation